From Victory to Peace Russian Diplomacy after Napoleon - Wirtschafter, Elise (NIU Series in Slavic, East European, and Eurasian Studies, 2020)
"In From Victory to Peace, Elise Kimerling Wirtschafter brings the Russian perspective to a critical moment in European political history. This history of Russian diplomatic thought in the years after the Congress of Vienna concerns a time when Russia and Emperor Alexander I were fully integrated into European society and politics. Wirtschafter looks at how Russia's statesmen who served Alexander I across Europe, in South America, and in Constantinople represented the Russian monarch's foreign policy and sought to act in concert with the allies. Based on archival and published sources-diplomatic communications, conference protocols, personal letters, treaty agreements, and the periodical press-this book illustrates how Russia's policymakers and diplomats responded to events on the ground as the process of implementing peace unfolded. Thanks to generous funding from the Sustainable History Monograph Pilot and the Mellon Foundation the ebook editions of this book are available as Open Access (OA) volumes from Cornell Open (cornellopen.org) and other Open Access repositories."